Pengaruh Pemberian Kompos Bunga Jantan Kelapa Sawit dengan Pupuk NPK terhadap Pertumbuhan Bibit Kelapa Sawit (Elaesis guineensis Jacq.) di Pembibitan Utama - Harry Prastowo; Husna Yetti; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to know the right dose about effect interaction between compost (male flowers) and NPK fertilizer for the growth of palm oil nursery in main nursery. This research was conducted in September to January 2018. The research method used is complete randomized design (RAL) with two factors, fisrt factor are compost which have four taraf such dose 60 g/polybag, 120 g/polybag, 180 g/polybag, 240 g/polybag and second factor NPK fertilizer with two taraf such as 5 g/plant and 10 g/plant. This study aims to improve plant growth, number of leaves, diameter of the cork, volume akar, rasio tajuk akar and berat kering bibit. Result of this study showed that application between compost and NPK fertilizer showed significanly effect to plant growth but didn’t effect to number of leaves, diameter of the cork, root volume, root canopy ratio, dry weight. Application of 240 g/polybag compost and 10g/plant NPK fertilizer showed higher means from ecah parameter. Keywords : oil palm, male flowers, fertilizer NPK